Management of natural service bulls on large dairies - Chenoweth, P.J.; Smith, John F., 1962- (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Natural service (NS) bulls are widely used on large dairy farms despite the wellproven genetic progress achievable through AI. Producers may choose to use NS bulls for a variety of reasons that are discussed below. In this presentation, problems encountered with the use of NS bulls on a large dairy in Kansas are described in relation to reduced reproductive performance on that dairy. Lameness in bulls was considered to be a major contributing factor to reduced herd reproductive performance, with seminal vesiculitis also possibly playing a role. Possible contributing factors for the occurrence of these problems in the bull population are discussed. A number of recommendations are made for optimal selection, use, and management of NS bulls. These include the following. Natural service bulls should preferably be younger bulls (< 2.5 years of age) and tractable. Facilities should be adequate for the safe handling of bulls and people. Attention should be paid to minimizing heat stress during the summer. An environment should be created where reproductive behavior can be fully expressed. Appropriate considerations include: sufficient space for courtship and breeding; minimizing distractions, such as people and noise; and the provision of suitable flooring for breeding (i.e., provision of secure footing). Natural service bulls should pass a breeding soundness evaluation prior to purchase and/or first use and this should be repeated at least annually. Bulls should undergo the same herd health procedures as the cow herd (except for brucella, trichomoniasis and MLV IBR vaccination). Particular attention should be paid to the prevention of venereal disease (vibriosis and trichomoniasis) transmission. Monitoring and record keeping for cows exposed to bulls should be similar to that for cows in AI groups and include regular pregnancy checks.
Keywords: Dairy; Bulls; Fertility; Lameness